Deconstructing neoliberal hegemony - Lotz, Corinna; Cole, Penny (Cadernos do GPOSSHE On-line, 2019)
Neoliberal hegemony or power is seen as the contemporary form of capitalism, a social-historical formation with three dialectically-related aspects: the state, the economic system and ideological systems. These exist side by side and are interconnected and inter-dependent but they are not identical. Considering these aspects “in themselves” is a challenge, because the economic foundations of neoliberal capitalism are frequently viewed as a seamless, monolithic, omnipotent social system.The paper examines the contradictions with the neoliberal Ideal, drawing on the approach of the oppositional Soviet philosopher Evald Ilyenkov. The Ideal is internally contradictory and therefore “unquiet” with the power to stimulate action. It exists in a negated way within the individual but also has an independent existence outside the individual. It is objective because it is not the property of, or nor does it arise from one individual’s actions in the world: it is the objective form of the whole social existence of human beings.